INDÍCIOS DE AUTORIA EM TEXTOS DE OPINIÃO ESCOLARES ESCRITOS POR ALUNOS DE 6º ANO DO ENSINO FUNDAMENTAL - Mendes, Sueli de Freitas (2013)
Evaluation of text in elementary school has been accomplished, in most cases, taking grammar and/or textual aspects into account. Under this perspective, a text is considered good since it meets grammar and/or textual order requirements. I understand, however, following Possenti (2009a) that, to consider a school text as a good one, it is necessary to evaluate it in its discursive aspects, that is why I take authorship in school texts, a case of study in this dissertation. In order to do that, I analyze argumentative texts written by 6th grade elementary school students, adopting (GINZBURG, 1989)'s signs paradigms as a theoretical-methodological procedure, an investigative procedure primarily qualitative and interpretative. The question guiding the work is: is there, in school argumentative texts written by ES 6th grade students, signs of singularity that indicate a movement of authorship? To answer it, my statement relies on the new authorship concept proposed by Possenti (2009a) to evaluate school texts, which allows to observe discursive aspects in those texts. According to the researcher, authorship in school texts must be thought along with singularity and style notion, by means of textual signs it is possible to detect it. Under this perspective, grammar correction and textual organization are not indication of authorship, its marks come from discourse order. It is also considered giving voice to other enunciators, keeping distance from one's own text, avoiding monotony as attitudes of an author. It is “how” it is said and not “what” is said that indicate authorship. In order to carry out the analyses, I turn to De Lemos' (2002) ideas about language acquisition, since 6th grade ES students are in a unique moment of written language acquisition. The author takes a theoretical positioning that opposes the notion of cognitive development in the interpretation of language acquisition process. For De Lemos (2002), changes that occur in children speech/writing cannot be considered as a result of increasing development or as a knowledge construction. Changes that occur in children speech/writing would be changes of children's position in relation to the speech/writing of another, in relation to the language and, consequently, in relation to the child's own speech/writing.Incorporation of arguments is frequent in the analyzed texts. What has been understood as a simple copy or repetition is the evidence of the position taken by the student-subject in his relationship with language – he, sometimes, is spoken by the other. However, in other texts, even repeating, the enunciator subject becomes singular, becomes author, evidencing himself in his relationship with language – performing strategies to show the work of the “self”. In the corpus analyzed by me,the uniqueness of the self enunciator manifests itself in several ways: it is assumed as a "self" child in relation to the proposed questioning, creating a facing/denial about the "politically correct speech"; it emerges as it shows itself divided, exposing the conflict experienced; self defining when attempting to define the other; it marks its singularity explaining its opinion in a narrative text and not in an argumentative school text.